2022
DOI: 10.31083/j.fbl2712323
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin, the Ingredient of Xihuang Pills, Inhibits Hepatocellular Carcinoma by Regulating Autophagy and Macrophage Polarization

Abstract: Background:The key active component(s) in an anti-tumor preparation used in traditional Chinese medicine, Xihuang Pills, remains unclear. Methods: We used a network pharmacology analysis to construct a component-disease-target network diagram and used this to determine quercetin as a critical active ingredient in Xihuang Pills. Subsequently, human hepatocellular carcinoma (HCC) cell lines, H22 and HepG2 cells, were treated with quercetin, and BALB/c mice were injected with H22 cells and treated with different … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 55 publications
0
5
0
Order By: Relevance
“…The top five active ingredients identified in our screening are MOL000098, MOL000422, MOL000449, MOL000006, and MOL000354, corresponding to quercetin, kaempferol, stigmasterol, luteolin, and isorhamnetin. Studies have shown that quercetin is involved in HCC autophagy (Wu et al, 2022), kaempferol inhibits HCC cell migration (Ju et al, 2021), luteolin enhances the efficacy of chemotherapy drugs (Xu et al, 2016), and isorhamnetin prevents liver fibrosis through oxidative stress (Yang et al, 2016). Funnel diagram of ORR.…”
Section: Discussionmentioning
confidence: 99%
“…The top five active ingredients identified in our screening are MOL000098, MOL000422, MOL000449, MOL000006, and MOL000354, corresponding to quercetin, kaempferol, stigmasterol, luteolin, and isorhamnetin. Studies have shown that quercetin is involved in HCC autophagy (Wu et al, 2022), kaempferol inhibits HCC cell migration (Ju et al, 2021), luteolin enhances the efficacy of chemotherapy drugs (Xu et al, 2016), and isorhamnetin prevents liver fibrosis through oxidative stress (Yang et al, 2016). Funnel diagram of ORR.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on the effect of QUE on hepatocellular carcinoma cells showed that LC3II/I increases with the concentration of the compound used, while p62 decreases. The authors suggest that the activation of the NF-κB pathway, through its impact on p62 levels, could stimulate autophagy, as indicated by the decreased levels of IκBα and phosphorylated p65 [ 118 ]. These results are confirmed by studies carried out on lung cancer cells, where the use of QUE reduces the expression of the p62 protein and increases GFP-LC3B in a dose-dependent manner [ 119 ].…”
Section: Autophagymentioning
confidence: 99%
“…Similarly, another in vitro and in vitro study by Wu et al using H22, HepG2, and BALB/c mice showed that quercetin was able to inhibit HCC proliferation and migration and promote apoptosis in a dose-dependent manner. After treatment by gavage, quercetin produced a reduction in the volume and weight of liver tumors in BALB/c mice through macrophage polarization in coordination with the NF-κB pathway to modulate the autophagic process [ 165 ].…”
Section: Targeting Oxidative Stress With Natural Compounds In Liver P...mentioning
confidence: 99%